ENGLISH LOANWORDS IN MODERN UZBEK ADVERTISING: PHONOLOGICAL AND MORPHOLOGICAL ADAPTATION, FREQUENCY PATTERNS, AND ATTITUDES AMONG YOUNG CONSUMERS - Aktamova , Mushtariy; Samatullayev , Dilshod (Scientific practical conference, 2026)
The globalization of English products and services has led to widespread borrowing into Uzbek, particularly in commercial discourse where loanwords signal modernity and international appeal. This article examines the use of English loanwords in advertising materials in Uzbekistan, including flyers, billboards, and mass media. It analyzes their frequency of use across different fields, their phonological and morphological adaptation, and the attitudes of young consumers aged 18 to 30 toward these borrowings. The findings indicate that loanwords appear most frequently in the fashion and business sectors. These words are often selected because they retain their original phonological features while being morphologically adapted to Uzbek grammatical structures.